Risk Assessment, Risk Management, and Risk Communication of Welding Work at PT Dok and Perkapalan Surabaya (Persero). - Aditya1, I Made Muliatna2, Abdul Rohim Tualeka1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
PT Dok dan Perkapalan Surabaya Is one of the manufacturing industry sectors in which operational activities can cause accidents and work-related illnesses such as the activities of joining the ship’s hull parts, namely the welding process. The risk of welding work needs to be done risk management to determine the prevention of possible work accidents through Risk Assessment activities which are then communicated to all parties. The purpose of this study is to identify hazards, conduct risk assessments and study risk control on welding work. This research is a descriptive study with an observational approach. From the results of the risk assessment of the 3 stages with 7 job descriptions, the percentage of risk categories was obtained, namely high risk 43% and medium risk 57%, and there was no low risk category Control carried out as part of risk management went well but residual risk remained so need a strong commitment from human resources or management and awareness of the workers on the use of personal protective equipment in every work. Risk communication is carried out through coaching or training, conducting safety induction, safety talk, Safety campaigns such as the activity of installing banners, posters, conducting meetings of the Health and Safety Guidance Committee at the end of each month to discuss the problems that occur and make improvements.